The national regulation of pharmaceutical markets and the timing of new drug launches in Europe - Alexander Heuer; Malwina Mejer; Jennifer Neuhaus (Kiel Institute for the World Economy (IfW), 2007)
We analyze the impact of national pharmaceutical regulation on the launch delay of new chemical entities approved by the EMEA's centralized procedure. We find that direct price control regimes have a significantly negative impact on the launch timing. These results cannot be found when investigating the impact of indirect price controls. Our results show that Germany (65%) has the highest probability of experiencing an early launch, while it is the lowest in southern European countries (18% for Portugal and 19% for Greece). This difference accrues from both price regulation and market attractiveness, since southern European countries generally have lower prices. Due to the possibilities for parallel trade within the EU, pharmaceutical companies, by acting strategically, may further increase launch delays.
Keywords: I11; I18; L51; 330; pharmaceuticals; regulation; new chemical entity; parallel trade; Pharmazeutisches Produkt; Markteintritt; Arzneimittelrecht; Staatliche Preispolitik; EU-Staaten